Restarting antidepressant and antipsychotic medication after intentional overdoses: need for evidence-based guidance - Emma Tay; Andreas Sotiriou; Garry G. Graham; Kay Wilhelm; Leone Snowden; Richard O. Day (SAGE Publishing, 2019)
Intentional drug overdoses with antidepressant and antipsychotic medications are an increasingly common problem. Currently, there is little guidance with regard to reintroduction of these medications after intentional overdoses. We have used published toxicological and pharmacokinetic data to obtain factors which control the recovery from overdoses. From such data, we have proposed guidance regarding their reintroduction, provided there are no adverse effects or contraindications. Tentatively, we suggest that when adverse effects from the overdose are lost, treatment could recommence after a further mean half-life of elimination. Most antidepressant and antipsychotic drugs are metabolized by cytochrome P450 enzymes and, where cytochrome P450 inhibitors are co-ingested, serial plasma concentrations should optimally be obtained in order to assess a suitable time for reintroduction of the psychoactive drugs. We hope the proposals presented will stimulate research and discussion that lead to better guidance for clinicians concerning reintroduction of psychoactive medication after intentional overdose.